(3GdMeGjI GdeOfjI ddeSJgdc EdcJQhfjkG (B/ s - (3CMeO LeGd EHQGgje EHQGgje YeGQgs; (3eMeO TcQj SQhQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2015)
(3JgOa GdOQGSI Gdi JSdjW GdVhA Ydi GdMeGjI GdeOfjI ddeSJgdc EdcJQhfjkG hagegG LjOGG hhVY fXQjI eJcGedI dgG ef TCfg JSgjd JMOjO eaghe GdMeGjI hEf JMOjO XGgQgG ai fGMjJjf ehVhYjI hYedjI dGTc Gfg jTcd MeGjI bhjI ddeSJgdc Jchf dg MUfG JLGg eG jJYQV Gdjg ai YedjGJ GdTQGA GdJi jLQjgG ef ZT hJLdjS hNOGY hZHf hZjQgG ef WQb GdGMJjGd hGdbGA GdVhA Ydi LgGR MeGjI GdeSJgdc hGdJMOjGJ GdJi jhGLggG heG GdebJQMGJ GdJi jecf Gf JDOi Gdi MeGjI aYGdg ddeSJgdc EdcJQhfjGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi (B2015s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B234-260s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdeOfjs; (3GdMeGjI GdeOfjI s; (3GdYbhO GdGSJgdGcjI GdGdcJQhfjIs; (3GdeSJgdc s; (3VeGf GdYjhH GdNajIs; (3GdJMcje GdGdcJQhfjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs